2022
DOI: 10.3390/cancers14041012
|View full text |Cite
|
Sign up to set email alerts
|

Repair-Assisted Damage Detection Reveals Biological Disparities in Prostate Cancer between African Americans and European Americans

Abstract: African Americans (AA) are two times more likely to be diagnosed with and succumb to prostate cancer (PCa) compared to European Americans (EA). There is mounting evidence that biological differences in these tumors contribute to disparities in patient outcomes. Our goal was to examine the differences in DNA damage in AA and EA prostate tissues. Tissue microarrays with matched tumor-benign adjacent pairs from 77 AA and EA PCa patients were analyzed for abasic sites, oxidative lesions, crosslinks, and uracil con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The results of a prostate cancer study showed that XRCC1 protein expression is reduced in AA tumors compared with EA tumors ( P = 0.0005; ref. 51 ) and PARP1 protein expression is similar between tumors of each racial cohort ( P = 0.1562).…”
Section: Nuclear Roles Of Parp1 In Cancer Progressionmentioning
confidence: 87%
“…The results of a prostate cancer study showed that XRCC1 protein expression is reduced in AA tumors compared with EA tumors ( P = 0.0005; ref. 51 ) and PARP1 protein expression is similar between tumors of each racial cohort ( P = 0.1562).…”
Section: Nuclear Roles Of Parp1 In Cancer Progressionmentioning
confidence: 87%
“…RADD offers several advantages over traditional techniques, including high sensitivity, the ability to detect multiple types of damage, and the capacity to study repair dynamics within cells. RADD has been successfully utilized for characterizing DNA damage in fixed cells and tissue sections [44] , [45] , [46] , in global genomic DNA samples at high-throughput [47] , and in DNA sequencing for genomic mapping [48] . Nevertheless, single-molecule detection as summarized in this report holds the highest sensitivity, with access to basal DNA damage levels and the potential of multiplexing with other epigenetic information.…”
Section: Discussionmentioning
confidence: 99%